2015
DOI: 10.1371/journal.pone.0116510
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors of Antenatal Anxiety and Depression in Pakistan: Is Social Support a Mediator?

Abstract: IntroductionPregnancy is generally viewed as a time of fulfillment and joy; however, for many women it can be a stressful event. In South Asia it is associated with cultural stigmas revolving around gender discrimination, abnormal births and genetic abnormalities.MethodologyThis cross-sectional study was done at four teaching hospitals in Lahore from February, 2014 to June, 2014. A total of 500 pregnant women seen at hospital obstetrics and gynecology departments were interviewed with a questionnaire consistin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
170
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(193 citation statements)
references
References 47 publications
16
170
6
1
Order By: Relevance
“…Similar to what is shown in the literature, in this study the risk of anxiety in pregnancy was higher among pregnant women who did not perform paid work activities (20) , highlighting employment as a protective factor for their mental health. This finding contrasts a Pakistani study, which showed that pregnant women working outside the household were more anxious and depressed than housewives who did not engage in labor activity (8) . Several factors may elucidate the findings of this study.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Similar to what is shown in the literature, in this study the risk of anxiety in pregnancy was higher among pregnant women who did not perform paid work activities (20) , highlighting employment as a protective factor for their mental health. This finding contrasts a Pakistani study, which showed that pregnant women working outside the household were more anxious and depressed than housewives who did not engage in labor activity (8) . Several factors may elucidate the findings of this study.…”
Section: Discussioncontrasting
confidence: 95%
“…Although maternal anxiety indexes during pregnancy are heterogeneous, anxiety symptoms and disorders are common in the perinatal period (3)(4) , and the symptoms may range from mild to severe (5) . National and international studies point to variable anxiety indexes around 23% in a study conducted in Alberta, Canada (6) , 15.6% in a study carried out in Germany (7) and 49% in Pakistan (8) .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, parity showed a direct and indirect relationship with psychological stress, therefore, parity can lead to anxiety through coping mechanism and psychological stress. The result of this study was in line with a study by Waqas et al, (2015). Parity is the condition of women related to the birth of a living child (Dorland, 2002).…”
Section: The Relationship Between Familysupporting
confidence: 89%
“…Family support, age, parity, stress, low economic status, birth history, history of violence are frequently reported predictors (Waqas et al, 2015;Meulen, 2016). Prenatal depression, poor pregnancy history, poor family relationships, low socioeconomic status, low education level, unwanted pregnancies, complications during pregnancy are the determinants of anxiety and labor pain (Meulen, 2016).…”
Section: Introductionmentioning
confidence: 99%